2003
DOI: 10.1002/cncr.11225
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial lesions in prophylactic mastectomy specimens from women with BRCA mutations

Abstract: BACKGROUNDIt has been suggested that BRCA‐associated breast carcinoma may often lack a detectable preinvasive phase. To investigate this hypothesis, the authors compared the prevalence of histopathologic lesions in prophylactic mastectomy (PM) specimens from women with BRCA mutations and in mastectomy specimens obtained at autopsy from an age and race‐matched comparison group without a known cancer predisposition.METHODSAll specimens from women with a deleterious BRCA1 or BRCA2 mutation who participated in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 33 publications
3
45
1
2
Order By: Relevance
“…40 Two groups have evaluated the prevalence of high-risk lesions (including ALH, atypical ductal hyperplasia, lobular carcinoma in situ, and DCIS) in prophylactic mastectomy specimens from women who were at increased genetic risk and found incidences of 46% and 57%. 41,42 Those study populations were comparable to ours with regard to age, BRCA1/ BRCA2 mutation status, and prior risk reduction with tamoxifen and/or BSO. In the current study, it was found that 4 of 41 patients (9.8%) had DCIS or highrisk findings, including ALH and radial scars.…”
Section: Discussionsupporting
confidence: 66%
“…40 Two groups have evaluated the prevalence of high-risk lesions (including ALH, atypical ductal hyperplasia, lobular carcinoma in situ, and DCIS) in prophylactic mastectomy specimens from women who were at increased genetic risk and found incidences of 46% and 57%. 41,42 Those study populations were comparable to ours with regard to age, BRCA1/ BRCA2 mutation status, and prior risk reduction with tamoxifen and/or BSO. In the current study, it was found that 4 of 41 patients (9.8%) had DCIS or highrisk findings, including ALH and radial scars.…”
Section: Discussionsupporting
confidence: 66%
“…According to Veronesi et al (28), higher histological grade and lymph node invasion were significantly more frequent in patients with high genetic risk. Moreover, we also found that patients with higher risk mutation proved to be significantly associated with the presence of vascular peri- ONCOLOGY REPORTS 23: 1641-1645, 2010 Table II. Risk of BRCA gene mutations in relation to clinicopathological features.…”
Section: Discussionmentioning
confidence: 53%
“…Atypical lobular and ductal hyperplasias were the more frequent lesions, followed by lobular and ductal carcinoma in situ (DCIS) Kauff et al, 2003). In a recent report , high-risk histopathology lesions were found in almost all (14 out of 15 women) of women older than age 40 years at high genetic risk of breast cancer with no demonstrable BRCA1/2 mutation but only 50% in BRCA1/2 mutation carriers.…”
Section: Premalignant Lesionsmentioning
confidence: 99%